KEWENANGAN PENEGAKAN HUKUM DI BIDANG LALU LINTAS ANTARA PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) DAN POLRI DITINJAU DARI UNDANG-UNDANG RI NO 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI LINGKUNGAN DINAS PERHUBUNGAN KABUPATEN GARUT - Gun Gun Nugraha; Joko T Suroso; Dudu Duswara Machmudin (Iustitia Omnibus (Jurnal Ilmu Hukum), 2019)
The emergence of Civil Servant Investigators (PPNS) as institutions outside the National Police to assist police duties in conducting investigations is strictly regulated in the Criminal Procedure Code and the Law of the Republic of Indonesia No.2 of 2002 concerning the Indonesian National Police. From the two laws, it is clear that the existence of the Civil Servant Investigator (PPNS) in the investigation process is at the level of helping, so that control over the investigation process remains with the police.This study aims to determine the role of the Civil Servant Investigator (PPNS) of the Department of Transportation and the implementation of Law Number 22 Year 2009 concerning Road Traffic and Transport and to determine the obstacles and solutions to overcome these obstacles. This research method is a type of normative legal research. Sources of data obtained from secondary data, namely primary, secondary and tertiary legal sources. Data collection methods through library research. Data analysis techniques used are qualitative data analysis with inductive methods.Based on the results of the study it can be concluded that, the Authority of Civil Servant Investigators (PPNS) of the Department of Transportation in enforcing Law Number 22 Year 2009 Regarding Road Traffic and Transport is as a technical implementer of the law, so that all actions owned and carried out by the Employee Investigator Civil Affairs (PPNS) Transportation Department in the enforcement of traffic and road transportation must be based on and in accordance with applicable laws and regulations. Authority of Civil Servant Investigators (PPNS) of the Department of Transportation within the scope of traffic and road transportation at terminals and weigh bridges.